Robust micropatterns on graphene oxide films based on the modification of fluorescence lifetime for multimode optical recording. (February 2019) - Qiao, Zhixing; Qin, Chengbing; He, Wenjun; Gong, Yani; Li, Bin; Zhang, Guofeng; Chen, Ruiyun; Gao, Yan; Xiao, Liantuan; Jia, Suotang
Abstract: Here we report on the fine modification of fluorescence lifetime of graphene oxide (GO) film by introducing a localized writing process with a well-controlled reduction degree. The modification results from the elimination of long-lived sp 3 functional groups and/or the conversion of that to short-lived sp 2 confined clusters. By optimizing the parameters of writing process, four-lifetime distributions with narrow width have been determined. The distinguishable lifetime distributions allow to create versatile and complex micropatterns on the GO film, which are robust with film-thickness- and reading-power-independent features. These features enable a multimode optical recording on GO film for high-capacity information storage based on the contrast of fluorescence lifetime. Our results present that lifetime modification of GO film can provide a new platform for the fabrication of micro-photonic information devices. Graphical abstract: Image 1